Redisigning career plan and development to optimize pt krakatau daya listrik performance - Diah Kartika Irawati, Monica Rahayu Siska; Welly, John (The Indonesian Journal of Business Administration, 2018)
Abstract. Since PT Krakatau Daya Listrik (KDL) established as subsidiary PT Krakatau Steel Tbk. (PT KS) on 1996, business process and strategy of PT KDL should be supported PT KS goals. Focus in Human Capital development evaluation, to achieve PT KDL target there are some issues as obstacles of PT KDL. Career planning & development system cannot fulfilled what employee needs and cannot supports PT KDL achievement. Based on analysis from employee satisfaction survey and SWOT PT KDL in Rencana Jangka Panjang Perusahaan (RJPP 2017-2021), PT KDL should gain more information to find out the root cause and compare with literature for redesigning the system. Design alternative should be present to expert representative Human Capital from several company and to Board of Directors. Root cause of this problem issue not only related with system of career planning, but start from implementation and how to  assess in performance management system. To overcome the issues, PT KDL should create new design start from performance management to develop people and implemented in career planning and development to optimize company performance. Keywords:  performance management, career planning, career development